Incidental and symptomatic renal tumors: impact on patient survival - Dall’Oglio, Marcos Francisco; Srougi, Miguel; Gonçalves, Pierre Damião; Leite, Kátia; Nesrallah, Luciano; Hering, Flávio (São Paulo Medical Journal, 2002)
CONTEXT: Renal cell carcinoma is the third most frequent genitourinary neoplasia, and there is currently an increase in the incidental diagnosis of tumors confined to the kidneys. OBJECTIVE: To study the survival of patients with incidental and symptomatic renal tumors who have undergone nephrectomy. DESIGN: Retrospective. SETTING: Hospital Sírio Libanês and Beneficência Portuguesa de São Paulo. PARTICIPANTS: 115 patients with diagnosis of renal cell carcinoma, operated on by the same group of surgeons and evaluated by a single pathologist. MAIN MEASUREMENTS: Sex, age and diagnosis method, analyzed in two groups, according to the tumor diagnosis: Group 1 with incidental diagnosis and Group 2 with symptomatic tumors. The anatomopathological characteristics and patient survival in both groups were evaluated. A statistical analysis was performed using the Student t, chi-squared, log rank and Kaplan-Meyer tests. RESULTS: Among the studied patients, 59(51%) had an incidental diagnosis, with 78% diagnosed by ultrasonography, 20% by computerized tomography scan and 2% during surgeries; 56 patients (49%) were symptomatic. Tumor locations were equally distributed between the two kidneys, and the surgery was conservative for 24% of the incidental and 9% of the symptomatic group. In the incidental group only one patient had tumor progression and there was no death, while in the symptomatic group there were 5 progressions and 10 deaths. The 5-year specific cancer-free survival was 100% in the incidental and 80% in the symptomatic group (p = 0.001) while the disease-free rate was 98% in the incidental and 62% in the symptomatic group (p < 0001). CONCLUSION: Incidental renal tumor diagnosis offers better prognosis, providing longer diseasefree survival.